Recomendações para (re)design da visualização em ferramentas de monitoramento de redes - Oliveira, Hélio Tibagí de (2018)
Monitoring tools have evolved over the years to keep support of advances in computer network technology, adapting to new paradigms such as virtualization, software orientation, and more recently a programmable data plan. However, few advances have been made in the area of interface and interaction in network management systems, nor to know about the main actor, the network administrator, who uses these tools to solve problems and make decisions. Thus, in the current dissertation we present a investigation based on the HCI perspective, through the analysis of data collected in both field researches and experimental approaches, which together enabled the development of recommendations for software developers to the (re)design of data in network monitoring tools.